PERANAN PEMERINTAH DAERAH KABUPATEN SAMBAS TERHADAP PELESTARIAN CAGAR BUDAYA BERDASARKAN UNDANG-UNDANG - YOHANDAWAN, VERA PURNAMA (Lunggi Journal, 2024)
The objective of this research is to understand the role of the Sambas Regency Government (Department of Education and Culture) in preserving cultural heritage. This research uses an empirical juridical method and field research, with data collection techniques through observation, interviews, and documentation. The researcher also applied a descriptive analytical approach, which aims to reveal problems, situations, and events as they are, making it factual. The descriptive analytical approach also accurately describes the characteristics of an individual, situation, phenomenon, or specific group concerning existing regulations. The results of this research indicate that the Department of Education and Culture of Sambas Regency plays an important role in the management and preservation of cultural heritage in accordance with the applicable regulations. In addition to technical tasks in the field of education and culture, the department serves as a regulator and facilitator to raise public awareness about the importance of cultural heritage. Through policies, socialization, and promotion, the department encourages public participation in preservation efforts. Despite challenges such as budget limitations, the department has provided information, communicated with community leaders, and addressed disasters related to cultural heritage. However, some efforts still need improvement. In terms of preserving cultural heritage in Sambas Regency in accordance with Law Number 11 of 2010, there are both supporting and inhibiting factors. Supporting factors: Public awareness of history and local culture remains high, as evidenced by the enthusiasm for visiting museums and historical tourist sites such as the Sambas Palace. The community highly values the region's cultural wealth. Inhibiting factors: Budget constraints and a lack of experts are the main obstacles. The Department of Education and Culture faces difficulties in making innovations due to limited funds, and the lack of experts hinders the data collection and prioritization of cultural heritage preservation efforts.